The effect of counseling based on acceptance and commitment therapy on anxiety, depression, and quality of life among female adolescent students - Sayeh Shiri; Azizeh Farshbaf-Khalili; Khalil Esmaeilpour; Niloofar Sattarzadeh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Adolescence is a stressful time period. Adolescents experience new changes physically, mentally, emotionally, and socially. The purpose of this study was to determine the effects of acceptance and commitment therapy (ACT) on anxiety (primary outcome), depression, and quality of life (secondary outcomes) of adolescents. Materials And Method : This was a quasi-experimental study with pre and postintervention design. One hundred female students aged 16-18 years with mild to moderate anxiety selected through multistage cluster sampling from five educational districts of Tabriz. During six group counseling sessions, students were consulted with the acceptance and commitment approach according to the protocol. Beck Anxiety and Depression Inventory and the World Health Organization brief Quality of Life Questionnaire consultation were completed before, immediately after, and 8 weeks after the consultation. Data were analyzed using repeated measure ANCOVA. RESULTS: The mean anxiety score decreased significantly immediately after the intervention (mean difference [MD]: −4.0, 95% confidence interval [CI]: −5.9 to − 2.0; P < 0.001) and 8 weeks later (MD: −3.9, 95% CI: −5.8 to − 1.9; P < 0.001). The mean depression score immediately (P < 0.001) and 8 weeks after intervention (MD; −4.2, CI: −1.6 to − 6.8), P < 0.001) declined significantly. The mean overall quality of life score increased significantly after the intervention (P < 0.001) and 8 weeks later (MD: 4.7, 95% CI: 7.1-2.3, P < 0.001) compared to baseline. CONCLUSIONS: Based on the effectiveness of counseling based on ACT on anxiety, depression, and quality of life in the female students with the mild and moderate anxiety over time, it can be used as a helpful method in high schools.